Coronary artery disease surveillance among childhood, adolescent and young adult cancer survivors: A systematic review and recommendations from the International Late Effects of Childhood Cancer Guideline Harmonization Group. (October 2021) - van Dalen, Elvira C.; Mulder, Renée L.; Suh, Eugene; Ehrhardt, Matthew J.; Aune, Gregory J.; Bardi, Edit; Benson, Bradley J.; Bergler-Klein, Jutta; Chen, Ming H.; Frey, Eva; Hennewig, Ulrike; Lockwood, Liane; et al.
Abstract: Background: Coronary artery disease (CAD) is a concerning late outcome for cancer survivors. However, uniform surveillance guidelines are lacking. Aim: To harmonise international recommendations for CAD surveillance for survivors of childhood, adolescent and young adult (CAYA) cancers. Methods: A systematic literature review was performed and evidence graded using the Grading of Recommendations, Assessment, Development and Evaluation criteria. Eligibility included English language studies, a minimum of 20 off-therapy cancer survivors assessed for CAD, and 75% diagnosed prior to age 35 years. All study designs were included, and a multidisciplinary guideline panel formulated and graded recommendations. Results: 32 of 522 identified articles met eligibility criteria. The prevalence of CAD ranged from 0 to 72% and was significantly increased compared to control populations. The risk of CAD was increased among survivors who received radiotherapy exposing the heart, especially at doses ≥15 Gy (moderate-quality evidence). The guideline panel agreed that healthcare providers and CAYA cancer survivors treated with radiotherapy exposing the heart should be counselled about the increased risk for premature CAD. While the evidence is insufficient to support primary screening, monitoring and early management of modifiable cardiovascular risk factors are recommended. Initiation and frequency of surveillance should be based on the intensity of treatment exposures, family history, and presence of co-morbidities but at least by age 40 years and at a minimum of every 5 years. All were strong recommendations. Conclusion: These systematically assessed and harmonised recommendations for CAD surveillance will inform care and guide research concerning this critical outcome for CAYA cancer survivors. Highlights: Cancer survivors are at risk for premature coronary artery disease (CAD). Especially survivors treated with radiotherapy exposing the heart. This guideline provides recommendations for CAD surveillance. Early monitoring and management of modifiable risk factors is recommended. Key knowledge gaps regarding CAD in cancer survivors require further investigation.